2010
DOI: 10.1063/1.3455324
|View full text |Cite
|
Sign up to set email alerts
|

The origin of low water vapor transmission rates through Al2O3/ZrO2 nanolaminate gas-diffusion barriers grown by atomic layer deposition

Abstract: This paper reports on thin film gas-diffusion barriers consisting of Al2O3/ZrO2 nanolaminates (NL) grown by low-temperature (80 °C) atomic layer deposition. We show that reliable barriers with water vapor transmission rates of 3.2×10−4 g/(m2 day), measured at 80 °C and 80% relative humidity, can be realized with very thin layers down to 40 nm. We determine that ZrO2 acts as anticorrosion element in our NL. Furthermore, we demonstrate by x-ray photoemission spectroscopy that an aluminate phase is formed at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 20 publications
2
88
0
Order By: Relevance
“…ALD aluminum oxide has been studied extensively as a water vapor barrier, and its tendency to degrade is well documented. [35][36][37] One of very few reports on mechanical properties of alumina films is from 1969, 38 when it was reported that Young's modulus of Al 2 O 3 films is reduced as a function of absolute humidity. It has also been shown that it is difficult to measure inherent strength of alumina because even low humidity in the range of 10-40% RH is affecting the results.…”
Section: Resultsmentioning
confidence: 99%
“…ALD aluminum oxide has been studied extensively as a water vapor barrier, and its tendency to degrade is well documented. [35][36][37] One of very few reports on mechanical properties of alumina films is from 1969, 38 when it was reported that Young's modulus of Al 2 O 3 films is reduced as a function of absolute humidity. It has also been shown that it is difficult to measure inherent strength of alumina because even low humidity in the range of 10-40% RH is affecting the results.…”
Section: Resultsmentioning
confidence: 99%
“…Formation of an aluminate phase of Al 2 O 3 and ZrO 2 in binary systems by alloying ZrO 2 and Al 2 O 3 has been reported. 21 Similarly, it is expected that electronbeam treatment induced Al 2 O 3 /TiO 2 phase transformation from an amorphous to Al 2 TiO 5 phase at the interface between the Al 2 O 3 and TiO 2 , as shown in Fig. 4b.…”
Section: Water Vapor Passivation Layer Preparationmentioning
confidence: 86%
“…Among these inorganic materials, multilayers consisting of Al 2 O 3 and ZrO 2 showed better barrier properties than the others [10,11]. Although there have been extensive studies of gas barrier layers with an inorganic/inorganic multilayer structure, most of them focused on the mechanism of barrier properties using a Ca-test method [12].…”
Section: Introductionmentioning
confidence: 99%